423 Safety and preliminary efficacy of intratumoral cavrotolimod (AST-008), a spherical nucleic acid TLR9 agonist, in combination with pembrolizumab in patients with advanced solid tumors. (10th December 2020) - O'Day, Steven; Perez, Cesar; Wise-Draper, Trisha; Hanna, Glenn; Bhatia, Shailender; Kelly, Ciara; Medina, Theresa; Laux, Douglas; Daud, Adil; Chandra, Sunandana; Shaheen, Montaser; Gao, Ling; et al.
Abstract : Background: Spherical nucleic acids (SNAs) are nanostructures consisting of radially oriented, densely packed oligonucleotides arranged in a spherical 3D architecture. SNAs have different properties than linear oligonucleotides, including increased cellular uptake, which may enhance efficacy. Cavrotolimod (AST-008) is an SNA toll-like receptor 9 (TLR9) agonist designed to robustly activate innate and adaptive immune responses. Cavrotolimod is in development for the treatment of advanced solid tumors in combination with PD-1 blockade. Prior studies demonstrated that cavrotolimod, alone and in combination with PD-1 blockade, increased circulating levels of Th1-type cytokines and activated peripheral T cells and NK cells. Methods: AST-008-102 is an ongoing Phase 1b/2 study (NCT03684785 ). The Phase 1b dose escalation stage examined intratumoral (IT) cavrotolimod at doses of 2, 4, 8, 16, and 32 mg in combination with pembrolizumab in patients with advanced solid tumors. Cavrotolimod was dosed once weekly for 8 weeks and once every 3 weeks thereafter. The Phase 2 dose expansion stage is examining cavrotolimod 32 mg IT in combination with IV pembrolizumab for the treatment of advanced Merkel cell carcinoma (MCC) and in combination with IV cemiplimab for the treatment of advanced cutaneous squamous cell carcinoma (CSCC). Both cohorts are enrolling patients with documented progression of disease on PD-(L)1 blockade. This analysis provides interim results of the Phase 1b stage. Results: In the Phase 1b stage, 20 patients were enrolled across all planned dose levels. No dose-limiting toxicities, grade (G)4 toxicities, or treatment-related serious adverse events (AEs) were observed. The most common AEs were injection site reactions (ISRs) and flu-like symptoms. All treatment-related AEs were < G3 except agitation and ISR (1 each). At data cutoff, ORR is 21% (4 of 19 evaluable patients) in a heterogeneous population with solid tumors. All 4 responders (2 melanoma and 2 MCC patients) have ongoing responses, with duration of response exceeding 52 weeks in 2 patients. Three of 4 responders had disease progression on PD-1 blockade at the time of enrollment, and one patient had a prior response to PD-1 blockade, but subsequently relapsed off therapy. Regression of both injected and noninjected lesions was observed. Gene expression analyses demonstrated increased IT infiltration by cytotoxic immune cells in both injected and noninjected tumors. The highest dose (32 mg) was selected for the Phase 2 stage. Conclusions: IT administration of cavrotolimod appears to be safe and well tolerated in combination with pembrolizumab. Durable responses have occurred in patients previously experiencing progressive disease on PD-1 blockade. Trial Registration: NCT03684785 Ethics Approval: The study was approved by Institutional Review Boards of Dana-Farber Cancer Institute (IRB #18-584), John Wayne Cancer Institute (WIRB #20183064), University of Miami (IRB #20180957), University of Iowa (IRB #201810763), University of Cincinnati (WIRB #20183064), University of Washington (WIRB #20183064), MSKCC (IRB #20-174), UC San Francisco (WIRB #20183064), U Colorado (WIRB #20183064), Northwestern (IRB #STU00211083), U Arizona (WIRB #20183064), UC Irvine (WIRB #20183064), U Pitt (WIRB #20183064), and Washington University (WIRB #20183064).